Applying the Strategic Health Purchasing Progress Tracking Framework: Lessons from Nine African Countries. Issue 2 (1st March 2022) - Gatome-Munyua, Agnes; Sieleunou, Isidore; Barasa, Edwine; Ssengooba, Freddie; Issa, Kaboré; Musange, Sabine; Osoro, Otieno; Makawia, Suzan; Boyi-Hounsou, Christelle; Amporfu, Eugenia; Ezenwaka, Uchenna
ABSTRACT: The Strategic Purchasing Africa Resource Center (SPARC) developed a framework for tracking strategic purchasing that uses a functional and practical approach to describe, assess, and strengthen purchasing to facilitate policy dialogue within countries. This framework was applied in nine African countries to assess their progress on strategic purchasing. This paper summarizes overarching lessons from the experiences of the nine countries. In each country, researchers populated a Microsoft Excel–based matrix using data collected through document reviews and key informant interviews conducted between September 2019 and March 2021. The matrix documented governance arrangements; core purchasing functions (benefits specification, contracting arrangements, provider payment, and performance monitoring); external factors affecting purchasing; and results attributable to the implementation of these purchasing functions. SPARC and its partners synthesized information from the country assessments to draw lessons applicable to strategic purchasing in Africa. All nine countries have fragmented health financing systems, each with distinct purchasing arrangements. Countries have made some progress in specifying a benefit package that addresses the health needs of the most vulnerable groups and entering into selective contracts with mostly private providers that specify expectations and priorities. Progress on provider payment and performance monitoring has been limited. Overall, progress on strategic purchasing has been limited in most of the countries and has not led to large-scale health system improvements because of the persistence of out-of-pocket payments as the main source of health financing and the high degree of fragmentation, which limits purchasing power to allocate resources and incentivize providers to improve productivity and quality of care.